How do you solve the following equation using algebraic steps?:

2(4x-5) - 3(-x+6) =2/5(10x-65)

### 1 Answer | Add Yours

2(4x-5) - 3(-x+6) = (2/5)(10x-65)

First we will open the brackets.

==> 8x -10 + 3x -18 = (2/5)10x - (2/5)(65)

==> Now we will combine like terms.

==> 5x -28 = 4x - 26

Now we will subtract 4x from both sides.

==> x -28 = -26

Now we will add 28 to both sides.

==> x = 28-26 = 2

**Then the answer is x= 2.**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes